Characteristics of Electromagnetic Signals During the Initial Stage of Negative Rocket‐Triggered Lightning. Issue 20 (17th October 2018) - Fan, Yanfeng; Lu, Gaopeng; Jiang, Rubin; Zhang, Hongbo; Li, Xiao; Liu, Mingyuan; Qie, Xiushu; Zheng, Dong; Lyu, Weitao; Zhang, Yang; Zhang, Yijun
Abstract: With the measurements in SHandong Triggering Lightning Experiment and Guangdong Comprehensive Observation Experiment on Lightning Discharge in China, we examine the electromagnetic signals associated with the upward positive leaders during the initial stage of negative triggered lightning. The magnetic field ( B field) signals measured at close range (<100 m) for both sites can be divided into two categories (i.e., impulsive and ripple pulses) according to the discernibility of separation between individual pulses. The impulsive pulses are well simulated by using the transmission line model, which suggests that these pulses are generated by leader current pulses propagating downward along the steel wire. Because the length of extended leader channel ahead of the wire is not negligible during the stage of ripple pulses, the waveform of impulsive current pulses is changed after traveling through the high impedance leader channel. Taking the filtered current pulse as the input variable, the waveform of ripple pulse can be simulated properly, which indicates that ripple pulses are caused by the attenuation of impulsive current along prolonging leader channel. In addition, the paper analyzes the fast electric field ( E field) changes measured at 60‐m range from the launching site during the initial stage by using the transmission line model and shows that the polarity of E field change at a given range is determined by the inception height of upward leader, namely the surface E field change caused by the individual charge transfer of initial upward leader also involves the problem of reverse distance as present for a vertical dipole. Plain Language Summary: Lightning can occur at a predictable time and place by using the technique of rocket‐triggered lightning, which launches a small rocket trailing a grounded steel wire toward the charged thundercloud overhead. Therefore, the technique facilitates the research of lightning discharges and their electromagnetic effects. At the beginning of triggered lightning, a sustained train of current pulses can be measured at the base of discharge path, and the synchronous electromagnetic field signals can also be recorded by the electric and magnetic sensors deployed around the rocket launching site. The paper focuses on the characteristics of electromagnetic signals measured at close range (<100 m) during the SHandong Triggering Lightning Experiment and Guangdong Comprehensive Observation Experiment on Lightning Discharge (two experimental sites of triggered lightning in China) campaign. The main contributions of this article include two aspects: first, we clarify the relationship between the electromagnetic signals and current pulses during the initial stage of triggered lightning; second, we demonstrate the influences of the triggering height on the polarity of electric field waveform. Key Points: Both impulsive and ripple magnetic pulses in the measurements are produced by current pulses propagating downward along the discharge path The ripple pulses are caused by the attenuation of impulsive current along prolonging leader channel The polarity of electric field change at close range is determined by the inception height of triggered lightning